Evaluation of the Young Farmer Support in South Transdanubia - Szabó, Kinga; Horváthné Kovács, Bernadett; Koponicsné Györke, Diána (Acta Carolus Robertus, 2022)
Maintaining the retention capacity of the rural areas is one of the comprehensive aims of rural development, as the 2nd pillar of the Common Agricultural Policy. Fair income opportunities, available services, sustainable environment are key factors to make rural areas at least as attractive as the more urbanized parts of a regions. Younger generations are the most important target group of population retention throughout Europe. According to Eurostat data, only 11% of all farmers are under 40 in the EU member states. Therefore, supporting young farmers and promoting generational change have been measures of keeping the rural population in the countryside. In our paper, we present the development of young farmers’ support in Hungary. Based on empirical data the study analyses the results and successfulness of the program between 2014 and 2020. The data of the examined timeframe is compared with the results of the previous programming period. The upshot of these calculations shows the progressive effects of the changes in the EU programming and policy making. For the empirical analysis secondary data are provided by the Hungarian Ministry of Innovation and Technology which maintains the web-based database of project calls and results regarding the development programmes in Hungary.
Keywords: young farmers; rural development; Hungary; South Transdanubia; CAP